2020
DOI: 10.34154/2020-ejcs-0201-01-09/euraass
|View full text |Cite
|
Sign up to set email alerts
|

Role of Unani Medicine in Prevention and Treatment of Waba (Epidemics) including COVID-19: A Review

Abstract: Mankind has faced many hardships like natural disaster, drought and epidemics. Study focuses on epidemics caused by microbes.Unani medicine has a long experience in treating epidemic diseases because its history is as old as the history of human being itself. More or less entire of the civilisations throughout the history became the basis for evolution of Unani medicine. Hippocrates (460-380BC) regarded it asbothart and science, discussed the epidemics and wrote a book on Epidemics. Body is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Using North Blotting and human in vivo detection dose-dependent (IC50 value were 1.0 and 2.0 mmol assays, two substances of costunolide and dehydrocostus lactone, inhibited Hepatitis B surface antigen (HBsAg) was expressed in the liver cancer a HepA2 cell line derived from HepG2 cells. Bsed on observation, it was demonstrated that the tested substances showed significant HBV acitivity [36,67].…”
Section: Anti-virus/microbementioning
confidence: 92%
“…Using North Blotting and human in vivo detection dose-dependent (IC50 value were 1.0 and 2.0 mmol assays, two substances of costunolide and dehydrocostus lactone, inhibited Hepatitis B surface antigen (HBsAg) was expressed in the liver cancer a HepA2 cell line derived from HepG2 cells. Bsed on observation, it was demonstrated that the tested substances showed significant HBV acitivity [36,67].…”
Section: Anti-virus/microbementioning
confidence: 92%
“…Management of diarrhea: habb-ul aas (Myrtus communis L., Myrtaceae) and tabasheer (Bambusa bambos (L.) Voss, Poaceae) are also prescribed. Relieve thirst: Sheera tukhm e kahu (Lactuca sativa L., Compositae, seed paste) is given [2,5,15,24] . If pneumonia or pleurisy occurs, qairooti aarad karsana (10 g), Ayarig /Sibr/Aloe vera L. sap (1 g) and C. sativus L. stamen (1 g) are crushed, mixed and warmed slightly, then they are applied on the chest wall and covered with a cotton bandage Marham (Ayarig) warm local application [2,5] .…”
Section: Compound Formulation (Murakkabat) Prescribed During Covid 19mentioning
confidence: 99%
“…If pneumonia or pleurisy occurs, qairooti aarad karsana (10 g), Ayarig /Sibr/Aloe vera L. sap (1 g) and C. sativus L. stamen (1 g) are crushed, mixed and warmed slightly, then they are applied on the chest wall and covered with a cotton bandage Marham (Ayarig) warm local application [2,5] . To strengthening to the body organs: Khamira Gauzaban Ambari Jawaharwala 12 gm or Khamira Gauzaban 12 gm with silver foil paper [6,24] .…”
Section: Compound Formulation (Murakkabat) Prescribed During Covid 19mentioning
confidence: 99%